Organic richness, hydrocarbon potentiality, maturity, and timing of petroleum generation of the Cretaceous and Miocene source rocks in the central Gulf of Suez, Egypt. Issue 18 (16th September 2016) - El Nady, M. M.; Ramadan, F. S.; Hammad, M. M.; Lotfy, N. M.
ABSTRACT: Total organic carbon (TOC) and pyrolysis analysis of the Cretaceous and Miocene source rocks in the central Gulf of Suez were evaluated throughout the 25 rock samples collected from 6 formations, namely Wata, Raha, Nubia "A" (Cretaceous source rocks); and Nukhul, Zeit, and Belayim (Miocene source rocks) from Gharib-252, Gharib-153, Gharib-163, Gharib-164, Gharib-167, and Gharib-165 wells. These data are used to study the probabilities of the source rock in the Cretaceous and Miocene source rocks in the central Gulf of Suez for the hydrocarbon generation through identifying the organic richness, type of organic matters, and thermal maturation of these organic materials. The results revealed that the Cretaceous formations are immature source rocks, ranging from fair to good source rocks and have kerogen of type III and type III/II. Meanwhile, Miocene source rocks, ranging from immature to marginally mature source rocks, are considered to range from good to very good source rocks for potential generation of both oil and gas and are characterized by kerogen of type III/II and type II.